Composite sodium vanadium phosphate material, preparation method, application and energy storage device
Patent Information
- Application Number
- CN202411159395.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-08-22
AI Technical Summary
[0003]本发明所解决的技术问题在于克服现有技术中存在的磷酸钒钠材料电导率和循环性能差的缺陷,提供一种复合磷酸钒钠材料及制备方法、应用和储能器件
(2)本发明制备的复合磷酸钒钠材料具有优异电子导电性和电化学性能,尤其是具有较佳的放电比容量和循环性能。
Smart Images

Figure CN118929611B_ABST
Abstract
Description
Technical Field
[0001] This invention specifically relates to a composite sodium vanadium phosphate material, its preparation method, applications, and energy storage devices. Background Technology
[0002] Sodium-ion batteries are considered a key new low-cost energy storage technology due to their advantages such as low raw material costs, excellent low-temperature performance, and good rate performance. Cathode materials, as one of the most critical components of sodium-ion batteries, are crucial for achieving long range, long lifespan, and high safety. Among them, sodium vanadium phosphate (CNP) cathode materials are designed as cathode materials with high cycle life due to their structural stability, which can significantly improve the lifespan of sodium-ion batteries and thus reduce the cost per kilowatt-hour. However, this material has significant drawbacks: low electronic conductivity, slow sodium ion diffusion rate, and poor water and oxygen stability. Therefore, this type of material limits discharge rate and low-temperature performance, and the electrode performance decays rapidly during charge and discharge. Although modifying CNP with fluorine to prepare sodium vanadium fluorophosphate cathode materials can improve charge and discharge potential and energy density, the problems of poor ionic / electronic conductivity and cycle life remain unresolved. Currently, there are few process technologies that fundamentally improve the electronic conductivity and rate performance of CNP cathode materials from the perspective of material structure design, thus greatly limiting the industrial application of CNP batteries. Summary of the Invention
[0003] The technical problem solved by this invention is to overcome the shortcomings of poor electrical conductivity and cycle performance of sodium vanadium phosphate materials in the prior art, and to provide a composite sodium vanadium phosphate material, its preparation method, applications, and energy storage devices. The composite sodium vanadium phosphate material prepared by this invention has excellent electronic conductivity and electrochemical performance, especially superior discharge specific capacity and cycle performance.
[0004] The present invention solves the above-mentioned technical problems through the following technical solutions: This invention provides a method for preparing a composite sodium vanadium phosphate material, which includes the following steps: granulating and sintering a mixture containing sodium vanadium phosphate, metal sulfide carbide nanosheets and an organic carbon source to obtain the composite sodium vanadium phosphate material; The chemical formula of the metal sulfide carbide nanosheets is M2CQ2, where M is Nb and / or Ta, and Q is S and / or Se; the mass ratio of sodium vanadium phosphate to the metal sulfide carbide nanosheets is 100:(0.5-20), and the mass ratio of sodium vanadium phosphate to the carbon source is 100:(2-30).
[0005] In this invention, the sodium vanadium phosphate preferably participates in the reaction in particulate form.
[0006] In this invention, the sodium vanadium phosphate can be commercially available or prepared in-house. The preferred method for preparing the sodium vanadium phosphate includes the following steps: grinding a mixture of sodium and vanadium sources weighed according to stoichiometric ratio, and then calcining it at 400-900℃ for 2-12 hours under inert gas protection.
[0007] Wherein, when the sodium source is NaH2PO4 and the vanadium source is vanadium pentoxide, the molar ratio of the sodium source to the vanadium source is 3:1.
[0008] The inert gas can be conventional in the art, such as nitrogen. The calcination temperature is preferably 600-800°C, for example, 700°C. The calcination time is preferably 2-6 hours, for example, 4 hours.
[0009] In this invention, the metal sulfide carbide nanosheets are preferably one or more of Nb₂CSe₂, Ta₂CSe₂, and Nb₂CS₂, and more preferably Nb₂CSe₂ nanosheets. The sheet size of the metal sulfide carbide nanosheets can be 100 nm-10 μm, and the sheet thickness can be 5-20 nm.
[0010] In this invention, the method for preparing the metal sulfide carbide nanosheets preferably includes the following steps: Method 1: The metal sulfide carbide nanosheets are prepared by hydrothermal reaction of a hydrazine hydrate mixture containing metal sulfide carbide powder. Alternatively, method two: the metal sulfide carbide powder and copper powder are calcined and acid-washed to obtain the metal sulfide carbide nanosheets.
[0011] The preferred method for preparing the metal sulfur carbide powder includes the following steps: grinding and pressing a mixture of metal M source, carbon source, "sulfur source and / or selenium source" and catalyst weighed according to stoichiometric ratio, placing it in a reaction tube, evacuating and sealing the reaction tube, and then calcining it to obtain the powder.
[0012] The metal source M can be niobium powder and / or tantalum powder. The carbon source can be graphite. The sulfur source can be sulfur powder. The selenium source can be selenium powder. The catalyst can be one or more of hexachlorobenzene, chlorobenzene, and benzene. The molar ratio of the metal source M, the carbon source, and the sulfur source and / or selenium source is, for example, 2:1:2. The mass of the catalyst is preferably 0.5%-10% of the total mass of the metal source M, the carbon source, and the sulfur source and / or selenium source, for example, 1%, 3%, 5%, 6%, or 8%, more preferably 3%-8%.
[0013] The grinding operation and conditions can be conventional in the art, such as being carried out in a mortar. The tableting equipment can be conventional in the art, such as a tablet press. The tableting pressure is preferably 5-15 MPa, for example, 10 MPa. The reaction tube is preferably a quartz tube. After vacuuming, the vacuum degree of the reaction tube is preferably less than or equal to 10. -3 Pa. The sealing is generally achieved by heating and melting both ends of the reaction tube. The calcination temperature is preferably 800-1400°C, for example, 1200°C. The calcination time is preferably 2-8 hours, for example, 5 hours.
[0014] In Method 1, the concentration of the hydrazine hydrate mixture containing the metal sulfide carbide powder is preferably 30-80 mg / mL, for example, 50 mg / mL. This concentration refers to the ratio of the mass of the metal sulfide carbide powder to the volume of the hydrazine hydrate mixture containing the metal sulfide carbide powder. The solvent in the hydrazine hydrate mixture containing the metal sulfide carbide powder is generally a mixture of an aqueous solution of hydrazine hydrate and deionized water. The volume ratio of the aqueous solution of hydrazine hydrate to deionized water can be 1:(2-5), for example, 1:3.
[0015] In Method 1, the hydrothermal reaction is generally carried out in a reaction vessel. The temperature of the hydrothermal reaction can be 90-140℃, for example, 120℃. The time of the hydrothermal reaction can be 12-48 hours, for example, 18 hours, 24 hours, or 30 hours. According to conventional practice in the art, after the hydrothermal reaction is completed, washing and drying are generally required.
[0016] In Method Two, the molar ratio of the metal sulfide carbide powder to the copper powder can be 1:(0.5-2), for example, 1:1 or 1:1.5. The mixture generally needs to be ground before calcination. Calcination is generally carried out under an inert atmosphere, such as nitrogen. The calcination temperature is preferably 500-1000℃, for example, 600℃, 800℃, or 900℃. The calcination time is preferably 2-8 hours, for example, 4 hours. The acid used for pickling is preferably concentrated hydrochloric acid. The concentration of the concentrated hydrochloric acid is, for example, 12M. The pickling time can be 2-8 hours, for example, 6 hours. Pickling is generally carried out under stirring. The stirring speed can be 200-600 rpm, for example, 300 rpm. After pickling, washing and drying are generally required.
[0017] To better maintain the dispersion of the nanosheets, the metal sulfide nanosheets are generally formulated into a dispersion for storage.
[0018] In this invention, the organic carbon source may be one or more of glucose, sucrose, fructose and starch, preferably glucose and / or sucrose.
[0019] In this invention, the mass ratio of sodium vanadium phosphate to the metal sulfur carbide nanosheets is preferably 100:(0.5-10), for example 100:1, 100:3, 100:4, 100:5, 100:6 or 100:10.
[0020] In this invention, the mass ratio of sodium vanadium phosphate to the carbon source is preferably 100:(2-20), for example 100:5, 100:8, 100:10, 100:15 or 100:20.
[0021] In this invention, sodium vanadium phosphate, metal sulfur carbide nanosheets, and an organic carbon source are preferably mixed before granulation. The mixing speed can be 500-2000 rpm, for example, 1500 rpm. The mixing time can be 10-60 min, for example, 30 min.
[0022] In this invention, a small amount of solvent is generally added before granulation. For example, the sodium vanadium phosphate, the metal sulfide nanosheets, the organic carbon source and the solvent can be mixed before granulation; or one or more of the sodium vanadium phosphate, the metal sulfide nanosheets and the organic carbon source can be added to the reaction system in the form of a dispersion.
[0023] In this invention, the metal sulfide carbide nanosheets are preferably added to the reaction system in the form of a metal sulfide carbide nanosheet dispersion. The concentration of the metal sulfide carbide nanosheet dispersion is preferably 0.5-5 mg / mL, for example, 1 mg / mL or 2 mg / mL. This concentration refers to the ratio of the mass of the metal sulfide carbide nanosheets to the volume of the metal sulfide carbide nanosheet dispersion. The solvent in the metal sulfide carbide nanosheet dispersion can be one or more of ethanol, methanol, and deionized water, for example, ethanol.
[0024] In this invention, the granulation method is preferably spray granulation. Spray granulation is generally carried out in a spray granulator. The process parameters for spray granulation can be an inlet temperature of 170-220°C (e.g., 190°C) and an outlet temperature of 80-110°C (e.g., 95°C).
[0025] In this invention, the sintering is generally carried out under an inert gas atmosphere. The sintering temperature can be 400-800℃, for example 450℃, 500℃, 550℃ or 600℃, preferably 500-700℃. The sintering time can be 1-6h, for example 2h, 3h or 4h, preferably 1-3h.
[0026] The present invention also provides a composite sodium vanadium phosphate material prepared by the preparation method described above.
[0027] In this invention, the composite sodium vanadium phosphate material can be spherical or near-spherical in shape. The size of the composite sodium vanadium phosphate material can be 5nm-50μm, preferably 50nm-20μm.
[0028] This invention also provides an application of the aforementioned composite sodium vanadium phosphate material in sodium-ion batteries. Preferably, the composite sodium vanadium phosphate material is used as a positive electrode material.
[0029] The present invention also provides an energy storage device comprising the composite sodium vanadium phosphate material as described above.
[0030] The energy storage device is preferably a sodium-ion secondary battery, a sodium-ion capacitor, a sodium-air battery, a sodium-sulfur battery, or a derivative energy storage device.
[0031] All raw materials and reagents used in this invention are commercially available.
[0032] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention.
[0033] The reagents and raw materials used in this invention are all commercially available.
[0034] The positive and progressive effects of this invention are as follows: (1) The method described in this invention has a simple synthesis process and high raw material utilization rate, which is conducive to industrial production; (2) The composite sodium vanadium phosphate material prepared by the present invention has excellent electronic conductivity and electrochemical performance, especially with better discharge specific capacity and cycle performance. Attached Figure Description
[0035] Figure 1 SEM image of the Nb2CSe2 nanosheets prepared in Example 1; Figure 2 SEM image of the composite sodium vanadium phosphate material prepared in Example 1; Figure 3 The image shows the XRD pattern of the Nb2CSe2 powder prepared in Example 1. Figure 4 The image shows the XRD pattern of the Ta2CSe2 powder prepared in Example 8. Figure 5 The image shows the XRD pattern of the Nb2CS2 powder prepared in Example 9. Figure 6 The image shows the xrd plot of the Ta2CS2 powder prepared in Example 10. Detailed Implementation
[0036] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions. Example 1
[0037] (1) Vanadium pentoxide and NaH2PO4 were thoroughly ground and mixed in a molar ratio of 1:3 and then placed in a tube furnace. Under nitrogen atmosphere protection, the temperature was raised to 700℃ at a heating rate of 5℃ / min and held for 4h. After cooling, sodium vanadium phosphate particles were obtained. (2) Weigh out niobium powder, graphite powder, and selenium powder in a molar ratio of 2:1:2, then add hexachlorobenzene at 6% of the total mass of niobium powder, graphite powder, and selenium powder. Grind the mixture evenly in a mortar and pestle, then press it into thin sheets using a tablet press at a pressure of 10 MPa. Place the sheets in a quartz tube, evacuate the quartz tube, and seal it with an oxyhydrogen flame torch (vacuum degree less than 10). -3 The powder was transferred to a muffle furnace for calcination at a heating rate of 5℃ / min, a calcination temperature of 1200℃, and a calcination time of 5h. After cooling, Nb2CSe2 powder was obtained. Preparation of Nb2CSe2 nanosheets: Nb2CSe2 powder was weighed and prepared into a mixed solution with a concentration of 50 mg / mL. The solvent was a mixed solution of hydrazine hydrate and deionized water (the volume ratio of hydrazine hydrate to deionized water was 1:3, and the hydrazine hydrate was purchased from Aladdin). The solution was transferred to a reaction vessel and subjected to hydrothermal reaction at 120℃ for 24 hours. After cooling, the solution was filtered, washed, and dried to obtain intercalated Nb2CSe2 nanosheets. The Nb2CSe2 nanosheets were dispersed in ethanol to prepare a 1 mg / mL Nb2CSe2 nanosheet dispersion. (3) Sodium vanadium phosphate, Nb2CSe2 nanosheet dispersion and glucose were placed in a high-speed mixer and mixed at 1500 rpm for 30 minutes to obtain a precursor slurry; the precursor slurry was pumped into a spray granulator and sprayed granulation was performed under the conditions of an inlet temperature of 190℃ and an outlet temperature of 95℃. After granulation, the granulation material was transferred to a tube furnace and sintered under a nitrogen atmosphere. The sintering temperature was 600℃ and the sintering time was 2h; after sintering, the material was naturally cooled to room temperature to obtain a composite sodium vanadium phosphate material; wherein, the mass ratio of sodium vanadium phosphate to Nb2CSe2 nanosheets in the Nb2CSe2 nanosheet dispersion was 100:1, and the mass ratio of sodium vanadium phosphate to glucose was 100:10. Example 2
[0038] Compared with Example 1, except that the mass ratio of sodium vanadium phosphate to Nb2CSe2 nanosheets in step (3) is replaced with 100:3, all other parameters and conditions are the same as in Example 1. Example 3
[0039] Compared with Example 1, except that the mass ratio of sodium vanadium phosphate to Nb2CSe2 nanosheets in step (3) is replaced with 100:5, all other parameters and conditions are the same as in Example 1. Example 4
[0040] Compared with Example 1, except that the mass ratio of sodium vanadium phosphate to Nb2CSe2 nanosheets in step (3) is replaced with 100:10, all other parameters and conditions are the same as in Example 1. Example 5
[0041] Compared with Example 1, except that the mass ratio of sodium vanadium phosphate to glucose in step (3) is replaced with 100:5, all other parameters and conditions are the same as in Example 1. Example 6
[0042] Compared with Example 1, except that the mass ratio of sodium vanadium phosphate to glucose in step (3) is replaced with 100:20, all other parameters and conditions are the same as in Example 1. Example 7
[0043] (1) Same as Example 1; (2) The preparation of Nb2CSe2 powder is the same as in Example 1; Preparation of Nb2CSe2 nanosheets: Nb2CSe2 powder and high-purity copper powder were ground and mixed at a molar ratio of 1:1 and placed in a tube furnace. Under nitrogen atmosphere protection, the temperature was raised to 800℃ at a heating rate of 5℃ / min and held for 4h. After cooling, the mixture was placed in excess 12M concentrated hydrochloric acid and stirred at 300rpm for 6h. After filtration, the mixture was washed three times with water and ethanol and dried to obtain intercalated Nb2CSe2 nanosheets. The Nb2CSe2 nanosheets were dispersed in ethanol to prepare a 1mg / mL Nb2CSe2 nanosheet dispersion. (3) Same as in Example 1, a composite sodium vanadium phosphate cathode material was prepared. Example 8
[0044] (1) Same as Example 1; (2) Replace niobium powder with tantalum powder, and follow the same procedure as in Example 1 to obtain Ta2CSe2; (3) Except for replacing Nb2CSe2 with Ta2CSe2 prepared in step (2), the process is the same as in Example 1 to obtain the composite sodium vanadium phosphate cathode material. Example 9
[0045] (1) Same as Example 1; (2) Replace the selenium powder with sulfur powder, and follow the same procedure as in Example 1 to obtain Nb2CS2; (3) Except for replacing Nb2CSe2 with Nb2CS2 prepared in step (2), the process is the same as in Example 1 to obtain the composite sodium vanadium phosphate cathode material. Example 10
[0046] (1) Same as Example 1; (2) Replace niobium powder with tantalum powder and selenium powder with sulfur powder, and do the same as in Example 1 to obtain Ta2CS2; (3) Except for replacing Nb2CSe2 with Ta2CS2 prepared in step (2), the process is the same as in Example 1 to obtain the composite sodium vanadium phosphate cathode material. Example 11
[0047] Compared with Example 1, except that the percentage of hexachlorobenzene added in step (2) was adjusted from 6% to 1% of the solid mass, all other parameters and conditions were the same as in Example 1. Example 12
[0048] Compared with Example 1, except that hexachlorobenzene in step (2) is replaced with chlorobenzene, all other parameters and conditions are the same as in Example 1. Example 13
[0049] Compared with Example 1, except that glucose in step (3) is replaced with sucrose, all other parameters and conditions are the same as in Example 1. Example 14
[0050] Compared with Example 1, except that the sintering temperature in step (3) is adjusted to 450°C, all other parameters and conditions are the same as in Example 1. Example 15
[0051] Compared with Example 1, except that the sintering time in step (3) is adjusted to 4h, all other parameters and conditions are the same as in Example 1.
[0052] Comparative Example 1 The sodium vanadium phosphate material prepared in step (1) of Example 1.
[0053] Comparative Example 2 Compared with Example 1, except that the addition of Nb2CSe2 nanosheets was omitted in step (3), everything else was the same as in Example 1.
[0054] Comparative Example 3 Compared with Example 1, except that the addition of glucose was omitted in step (3), everything else was the same as Example 1.
[0055] Effect Example
[0056] (1) Morphological characteristics Figure 1 The image shows an SEM image of the Nb2CSe2 nanosheets prepared in Example 1. It can be seen that they are sheet-like nano-agglomerates with sheet sizes ranging from 200 nanometers to 5 micrometers and thicknesses of about 10 nanometers. Figure 2 The image shows a SEM image of the composite sodium vanadium phosphate material prepared in Example 1. After mixing and granulation, spherical particles ranging from 1 micrometer to 20 micrometers were obtained.
[0057] (2) Electrochemical performance testing The cathode materials prepared in Examples 1-15 and Comparative Examples 1-3 were used in button batteries for electrochemical performance testing. The battery assembly process is as follows: A positive electrode slurry was prepared by mixing positive electrode material, polyvinylidene fluoride (PVDF), and conductive carbon black in a mass ratio of 8:1:1 and dissolving them in N-methylpyrrolidone (NMP) solvent. The slurry was then uniformly coated onto aluminum foil to form a positive electrode sheet. The coated electrode sheet was placed in a vacuum drying oven at 120℃ and vacuum dried for 12 hours. The electrode sheet was then removed and cut into 12mm diameter circular sheets using a cutting machine. The active material loading on the positive electrode sheet was 3mg / cm³. 2 ; The battery was assembled using a glass fiber separator from Whatman Corporation; the electrolyte was 1M NaPF6, with EC (ethylene carbonate) and DMC (dimethyl carbonate) as solvents, in a volume ratio of EC:DMC = 1:1; a sodium metal sheet was used as the counter electrode; finally, the positive electrode, sodium sheet, spring sheet, gasket, positive electrode shell, negative electrode shell, separator, and electrolyte were assembled into a CR2025 coin cell in an argon-filled glove box. The charge / discharge voltage range was 2.0-4.1V, the initial charge / discharge rate was 0.1C, and the nominal specific capacity was 1C = 100mAh / g. Cycling performance was tested at a charge / discharge rate of 10C for 1000 cycles. The test results are shown in Table 1. Table 1 Example 1 115 109 92 Example 2 118 113 96 Example 3 120 115 96 Example 4 114 107 97 Example 5 112 92 90 Example 6 110 94 96 Example 7 113 108 93 Example 8 106 102 91 Example 9 107 104 92 Example 10 105 101 89 Example 11 109 103 88 Example 12 110 104 90 Example 13 112 107 94 Example 14 111 100 87 Example 15 112 105 90 Comparative Example 1 99 86 78 Comparative Example 2 100 89 82 Comparative Example 3 98 81 73 Based on the above experimental results, the composite sodium vanadium phosphate cathode material prepared by this invention has excellent electrochemical performance, with a 1C discharge specific capacity of over 105 mAh / g, a 10C discharge specific capacity of over 92 mAh / g, and an energy retention rate of over 88% after 1000 cycles.
[0058] According to Example 1 and Comparative Examples 1-3, when only sodium vanadium phosphate is used, without the addition of metal sulfur carbide nanosheets or organic carbon source, the 1C discharge specific capacity and 10C discharge specific capacity are reduced, especially the energy retention rate is as low as 73% after 1000 cycles.
[0059] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and the scope of protection of the present invention is defined by the appended claims. Those skilled in the art can make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but all such changes and modifications fall within the scope of protection of the present invention.
Claims
1. A method for preparing a composite sodium vanadium phosphate material, characterized in that, The process includes the following steps: granulating and sintering a mixture containing sodium vanadium phosphate, metal sulfide nanosheets and an organic carbon source to obtain the composite sodium vanadium phosphate material; The chemical formula of the metal sulfide carbide nanosheets is M2CQ2, where M is Nb and / or Ta, and Q is S and / or Se; the mass ratio of sodium vanadium phosphate to the metal sulfide carbide nanosheets is 100:(0.5-20), and the mass ratio of sodium vanadium phosphate to the carbon source is 100:(2-30).
2. The preparation method of the composite sodium vanadium phosphate material as described in claim 1, characterized in that, The preparation method satisfies one or more of the following conditions: (1) The preparation method of sodium vanadium phosphate includes the following steps: grinding a mixture of sodium source and vanadium source weighed according to the stoichiometric ratio, and calcining it at 400-900℃ for 2-12h under inert gas protection; (2) The metal sulfide nanosheets are one or more of Nb2CSe2, Ta2CSe2 and Nb2CS2; (3) The sheet size of the metal sulfide nanosheet is 100nm-10μm and the sheet thickness is 5-20nm; (4) The organic carbon source is one or more of glucose, sucrose, fructose and starch.
3. The preparation method of the composite sodium vanadium phosphate material as described in claim 2, characterized in that, The metal sulfide nanosheets are Nb2CSe2 nanosheets.
4. The preparation method of the composite sodium vanadium phosphate material as described in claim 2, characterized in that, The organic carbon source is glucose and / or sucrose.
5. The method for preparing the composite sodium vanadium phosphate material as described in claim 1, characterized in that, The preparation method satisfies one or more of the following conditions: (1) The metal sulfide carbide nanosheets are added to the reaction system in the form of a metal sulfide carbide nanosheet dispersion; (2) The mass ratio of sodium vanadium phosphate to the metal sulfur carbide nanosheets is 100:(0.5-10). (3) The mass ratio of sodium vanadium phosphate to the carbon source is 100:(2-20); (4) Before granulation, sodium vanadium phosphate, metal sulfide nanosheets and organic carbon source are mixed; (5) The granulation process parameters are: air inlet temperature 170-220℃ and air outlet temperature 80-110℃; (6) The sintering temperature is 400-800℃; (7) The sintering time is 1-6 hours.
6. The method for preparing the composite sodium vanadium phosphate material as described in claim 5, characterized in that, The concentration of the metal sulfide carbide nanosheet dispersion is 0.5-5 mg / mL.
7. The method for preparing the composite sodium vanadium phosphate material as described in claim 5, characterized in that, In the metal sulfur carbide nanosheet dispersion, the solvent is one or more of ethanol, methanol, and deionized water.
8. The method for preparing the composite sodium vanadium phosphate material as described in claim 5, characterized in that, The mass ratio of sodium vanadium phosphate to the metal sulfide carbide nanosheets is 100:1, 100:3, 100:4, 100:5, 100:6 or 100:
10.
9. The method for preparing the composite sodium vanadium phosphate material as described in claim 5, characterized in that, The mass ratio of sodium vanadium phosphate to the carbon source is 100:5, 100:8, 100:10, 100:15, or 100:
20.
10. The method for preparing the composite sodium vanadium phosphate material as described in claim 5, characterized in that, The mass ratio of sodium vanadium phosphate to the carbon source is 100:5, 100:8, 100:10, 100:15, or 100:
20.
11. The method for preparing the composite sodium vanadium phosphate material as described in claim 5, characterized in that, The sintering temperature is 450℃, 500℃, 550℃ or 600℃.
12. The method for preparing the composite sodium vanadium phosphate material as described in claim 5, characterized in that, The sintering temperature is 500-700℃.
13. The method for preparing the composite sodium vanadium phosphate material as described in claim 5, characterized in that, The sintering time is 2h, 3h or 4h.
14. The method for preparing the composite sodium vanadium phosphate material as described in claim 5, characterized in that, The sintering time is 1-3 hours.
15. The method for preparing the composite sodium vanadium phosphate material as described in claim 1, characterized in that, The preparation method of the metal sulfide carbide nanosheets includes the following steps: Method 1: The metal sulfide carbide nanosheets are prepared by hydrothermal reaction of a hydrazine hydrate mixture containing metal sulfide carbide powder. Alternatively, method two: the metal sulfide carbide powder and copper powder are calcined and acid-washed to obtain the metal sulfide carbide nanosheets.
16. The method for preparing the composite sodium vanadium phosphate material as described in claim 15, characterized in that, The preparation method of the metal sulfur carbide powder includes the following steps: grinding and pressing a mixture of metal M source, carbon source, "sulfur source and / or selenium source" and catalyst weighed according to stoichiometric ratio, placing it in a reaction tube, evacuating and sealing the reaction tube, and then calcining it to obtain the powder.
17. The method for preparing the composite sodium vanadium phosphate material as described in claim 16, characterized in that, The mass of the catalyst is 0.5%-10% of the total mass of the metal M source, the carbon source, and the "sulfur source and / or selenium source".
18. The method for preparing the composite sodium vanadium phosphate material as described in claim 17, characterized in that, The mass of the catalyst is 1%, 3%, 5%, 6% or 8% of the total mass of the metal M source, the carbon source and the "sulfur source and / or selenium source".
19. The method for preparing the composite sodium vanadium phosphate material as described in claim 17, characterized in that, The mass of the catalyst is 3%-8% of the total mass of the metal M source, the carbon source, and the "sulfur source and / or selenium source".
20. The method for preparing the composite sodium vanadium phosphate material as described in claim 16, characterized in that, The calcination temperature is 800-1400℃.
21. The method for preparing the composite sodium vanadium phosphate material as described in claim 20, characterized in that, The calcination temperature is 1200℃.
22. The method for preparing the composite sodium vanadium phosphate material as described in claim 16, characterized in that, The calcination time is 2-8 hours.
23. The method for preparing the composite sodium vanadium phosphate material as described in claim 22, characterized in that, The calcination time is 5 hours.
24. The method for preparing the composite sodium vanadium phosphate material as described in claim 15, characterized in that, The first method satisfies one or more of the following conditions: (1) The concentration of the hydrazine hydrate mixture containing metal sulfide carbide powder is 30-80 mg / mL; (2) In the hydrazine hydrate mixture containing metal sulfide carbide powder, the solvent is a mixture of hydrazine hydrate aqueous solution and deionized water; (3) The temperature of the hydrothermal reaction is 90-140℃; (4) The hydrothermal reaction time is 12-48h.
25. The method for preparing the composite sodium vanadium phosphate material as described in claim 24, characterized in that, The volume ratio of the hydrazine hydrate aqueous solution to the deionized water is 1:(2-5).
26. The method for preparing the composite sodium vanadium phosphate material as described in claim 15, characterized in that, Method 2 satisfies one or more of the following conditions: (1) The molar ratio of the metal sulfide carbide powder to the copper powder is 1:(0.5-2). (2) The calcination temperature is 500-1000℃; (3) The calcination time is 2-8 hours; (4) The acid used in the pickling is concentrated hydrochloric acid; (5) The pickling time is 2-8 hours.
27. A composite sodium vanadium phosphate material, characterized in that, It is prepared according to the preparation method of the composite sodium vanadium phosphate material as described in any one of claims 1-26.
28. The application of the composite sodium vanadium phosphate material as described in claim 27 in a sodium-ion battery.
29. An energy storage device, characterized in that, It includes the composite sodium vanadium phosphate material as described in claim 27.
30. The energy storage device as described in claim 29, characterized in that, The energy storage device is a sodium-ion secondary battery, a sodium-ion capacitor, a sodium-air battery, or a sodium-sulfur battery.
Citation Information
Patent Citations
Sodium vanadium phosphate composite cathode material and preparation method thereof
CN111994890A
Oxide-coated sodium battery positive electrode material as well as preparation method and application thereof
CN115425196A